Thomas Kirk's Students' Flora of New Zealand. Issue 1 (2nd January 2017) - Abbott, B.
ABSTRACT: Thomas Kirk (1828–1898) was one of New Zealand's leading botanists. The completed sections of his final work, The Students' Flora of New Zealand and the Outlying Islands, were published posthumously in 1899. This short communication outlines factors surrounding its initiation, and argues that Kirk deserves more recognition for describing New Zealand's indigenous plants and weeds in one sequence. The preparation of the Students' Flora also triggered arrangements to bring to New Zealand for the first time, specimens, plates and a manuscript resulting from Banks' and Solander's collections on Cook's first voyage in 1769.